Analisis Motivasi Kuliah sambil Bekerja pada Mahasiswa PGSD FKIP Universitas Widya Gama Mahakam Samarinda - Siska Oktaviani; Ahmad Syafi Adha (Universitas PGRI Semarang, 2020)
This research is done to know the motivation of what is behind the students run a lecture activity that requires science as a form of responsibility as a student and in addition also undergoes work activities that are working on a task to get wages or satisfaction. In this study, researchers used qualitative research with a case study approach, where researchers investigated carefully a program, event, activity, process, or group of individuals. The subject of this study is the students of the PGSD FKIP UWGM from the 2016 to 2019 class who are undergoing college activities while working. To obtain the necessary data in this study conducted various techniques such as observation, interviews, and documentation. Data analysis techniques conducted include data collection, data reduction, data presentation, and conclusion. Research findings show that the motivation of students to run a lecture while working because students ' desire to be independent and change their life for the better, by gaining a high education but they must fight the matter by working so that their needs are the cost of living, tuition fees, and other expenses can be fulfilled without having to ask with parents. And try to balance both activities in order to run well and support each other.